Children, their world, their education : final report and recommendations of the Cambridge Primary Review - Alexander, Robin J.; Armstrong, Michael; Flutter, Julia; Hargreaves, Linda; Harrison, David; Harlen, Wynne; Hartley-Brewer, Elizabeth; Kershner, Ruth; MacBeath, John; Mayall, Berry; Northen, Stephanie; Pugh, Gillian; et al. (Routledge, 2010)
'Children, Their World, Their Education' is more than a ground-breaking report. It is an unrivalled educational compendium. It assesses two decades of government-led reform. It offers a vision for the future. It goes to the heart of what education in a democracy is about.